Perbedaan Tingkat Kecemasan Anak Usia 6-9 Tahun pada Perawatan Gigi Sebelum dan Setelah Menggunakan Distraksi dengan Virtual Reality - Riyanto, Rezkha R.; Sembiring, Linda S.; Lesmana, Dian (e-GiGi, 2025)
Abstract: Anxiety is a major problem that contributes to the lack of cooperation among children undergoing dental treatment, particularly those aged 6-9 years. Physiologically, anxiety can be assessed through blood pressure and pulse rate measurement, and it can be reduced through distraction techniques. Active distractions are considered more effective because they involve the subjects directly, such as audiovisual distractions using virtual reality (VR). This study aimed to investigate the differences in blood pressure and pulse rate in relation to anxiety before and after distraction activities using virtual reality during dental treatment in children aged 6-9 years. This was a quasi-experimental study with a one-group pre-test and post-test design. Data were analyzed using the Wilcoxon test. The results obtained 33 children as subjects. The means blood pressure during extraction and restoration treatments were 100/68 mmHg and 99/66 mmHg before distraction, and 94/67 mmHg and 93/65 mmHg after distraction, respectively. The means pulse rate before extraction and restoration were 104 BPM and 100 BPM, and after distraction, they decreased slightly to 98 BPM and 93 BPM. The Wilcoxon test showed significant differences in systolic blood pressure, diastolic blood pressure, and pulse rate after distraction (p≤0.05). In conclusion, there was a significant difference (p<0.001) after the use of VR distraction towards anxiety during dental treatment in children aged 6-9 years. Keywords: children aged 6-9 years; anxiety; blood pressure; pulse; distraction; virtual reality Abstrak: Kecemasan merupakan penyebab kurangnya tingkat kooperatif anak ketika dilakukan perawatan di dokter gigi terutama pada anak usia 6-9 tahun. Secara fisiologis kecemasan dapat dinilai dari tekanan darah dan denyut nadi, yang dapat direduksi dengan menggunakan distraksi. Distraksi aktif dinilai lebih efektif karena melibatkan subjek secara langsung, contohnya distraksi audiovisual dengan virtual reality (VR). Penelitian ini bertujuan untuk mengetahui apakah terdapat perbedaan tekanan darah dan nadi sebelum dan setelah menggunakan alat VR terhadap kecemasan pada perawatan gigi anak usia 6-9 tahun. Jenis pnelitian ialah eksperimental semu dengan one group pre test- post test design. Analisis data menggunakan uji Wilcoxon. Hasil penelitian mendapatkan sebanyak 33 anak sebagai subjek penelitian. Sebelum diberikan distraksi rerata tekanan darah pada perawatan ekstraksi dan restorasi masing-masing 100/68 mmHg dan 99/66 mmHg, setelahnya 94/67 mmHg dan 93/65 mmHg. Rerata denyut nadi sebelum distraksi pada perawatan ekstraksi dan restorasi masing-masing 104 BPM dan 100 BPM, setelahnya 98 BPM dan 93 BPM. Hasil uji Wilcoxon mendapatkan perbedaan bermakna pada TDS, TDD, dan denyut nadi setelah distraksi dengan VR (p≤0,05). Simpulan penelitian ini yaitu terdapat perbedaan tekanan darah dan nadi yang bermakna setelah menggunakan virtual reality terhadap kecemasan anak usia 6-9 tahun pada perawatan gigi. Kata kunci: anak usia 6-9 tahun; kecemasan; tekanan darah; nadi; distraksi; virtual reality